Communication design for cultural heritage: disclose the identity of Ascoli Piceno experimenting with signs and symbols - Oppedisano, Federico Orfeo; Rossi, Daniele (DISEGNARECON, 2012)
The Design for the valorisation of cultural heritage, activates some skills useful for initiating systemic processes integrated, promoting a more suitable interaction between the actors involved in the valuation of assets. In particular, communication design is a discipline that operates in the contemporary age by relating different cultural topics. It contributes to the promotion of the heritage, using the potential offered by new forms of communication, creating new systems or tools to build effective and participatory communicative relations. In this framework, the article shows and explains some experiments, about visual artifacts for cultural heritage of the city of Ascoli Piceno in order to rediscover its identity and to improve its peculiarities, carried out during a creative workshop. The workshop proposed to combine different design methods in order to offer the opportunity to develop an original approach to visual design, able to identify, in visual form, properties and characteristic of the city and its territory, as well as effective configurations to communicate it to the community. For this reason the workshop provided some methodological guidelines for the development of a design process of visual identity, through the integration of traditional operating procedures, such as watercolour drawing, and digital, such as video mapping.